Four wave mixing suppression in optical systems through system parameters optimization - Abed H.J.; Din N.M.; Al-Mansoori M.H.; Abdullah F.; Fadhil H.A. (Maxwell Science Publications, 2023)
Four-Wave Mixing (FWM) is defined as an undesirable nonlinear effect that gives significantly degraded system performance and is expected to become the major drawback for optical communication systems. This study presents a method to suppress the FWM through system parameters optimization. The study was conducted on four different types of optical fiber, i.e., Single-Mode Fiber (SMF), Dispersion Shifted Fiber (DSF), Non-Zero Dispersion Fiber (NZDF) and Non-Zero Dispersion Shifted Fiber (NZDSF). The results proved that the optimization of the parameters can reduce the effect of FWM in optical fiber link. It showed that a maximum FWM power level was observed with DSF and a minimum FWM power level with SMF with little effect on the optical link channel. Moreover, the results demonstrated that the SMF type with reduced the input power and increased channel spacing decreases the effect of FWM power materialization to a minimum value with reduction rate of 22 dB in compared to varying other parameters. In the case of system performance with the optimization of (decreasing the input power and increasing channel spacing), the BER was 1.90×10-25 at received power of 7 dBm. However, in the presence of optimization (increasing both effective area and channel spacing) the BER was found to be less than 2.84×10-20 at same received power. © Maxwell Scientific Organization, 2014.